2016
DOI: 10.1161/circgenetics.115.001142
|View full text |Cite
|
Sign up to set email alerts
|

Novel Genetic Loci Associated With Retinal Microvascular Diameter

Abstract: Background There is increasing evidence that retinal microvascular diameters are associated with cardio- and cerebrovascular conditions. The shared genetic effects of these associations are currently unknown. The aim of this study was to increase our understanding of the genetic factors that mediate retinal vessel size. Methods and Results This study extends previous genome-wide association study results using 24,000+ multi-ethnic participants from 7 discovery and 5,000+ subjects of European ancestry from 2 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
35
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 30 publications
(40 citation statements)
references
References 50 publications
5
35
0
Order By: Relevance
“…Although we replicated previously reported loci for CRVE , we did not find any novel genome-wide significant loci for this trait[12]’[14]. In addition, we did not replicate any of the previously reported SNPs associated with CRAE [13].…”
Section: Resultssupporting
confidence: 47%
See 1 more Smart Citation
“…Although we replicated previously reported loci for CRVE , we did not find any novel genome-wide significant loci for this trait[12]’[14]. In addition, we did not replicate any of the previously reported SNPs associated with CRAE [13].…”
Section: Resultssupporting
confidence: 47%
“…Understanding the molecular genetic architecture of retinal vascular features provides a molecular pathophysiological basis linking retinal microvascular features with systemic vascular pathology. Recent genome-wide association studies (GWAS) found number of loci for widely investigated retinal traits including central retinal vein equivalent ( CRVE )[12–14], retinal arteriolar equivalent ( CRAE )[12–14], and optic disc morphology[15]. Evidence suggests retinal vascular tortuosity, another potentially important vascular parameter, is also associated with a range of cardiovascular risk factors [16,17].…”
Section: Introductionmentioning
confidence: 99%
“…Several studies revealed that there was no association with an arteriolar width decreasing and incident stroke and prevalent stroke rather venular widening was associated with incident stroke [ 18 , 129 ]. AVR was also analyzed to determine the relation between AVR and incident stroke and prevalent stroke as the arteriolar and venular widening is responsible for changing the value of AVR.…”
Section: Image Processing-based Blood Vessel Diameter Measurement mentioning
confidence: 99%
“…The nonsense mutation in TEAD1 found in the single subject of Aicardi syndrome similarly is predicted to affect transcription of downstream targets (Schrauwen et al 2015). A recent publication further reported that a SNP in TEAD1 (rs926971) may influence the size of the retinal microvasculature (Jensen et al 2016). Therefore, it is conceivable that variants in TEAD1 may contribute to the ocular and chorioretinal anomalies observed in a rare subset of girls with Aicardi syndrome.…”
Section: Introductionmentioning
confidence: 99%
“…A recent publication further reported that a SNP in TEAD1 (rs926971) may influence the size of the retinal microvasculature (Jensen et al. ). Therefore, it is conceivable that variants in TEAD1 may contribute to the ocular and chorioretinal anomalies observed in a rare subset of girls with Aicardi syndrome.…”
Section: Introductionmentioning
confidence: 99%